Employee epowerment - terminological and practical perspective - Anna Cierniak-Emerych; Katarzyna Piwowar-Sulej (Institute of Economic Research (IER), 2017)
The 1980s saw popularisation of the management paradigm requiring that employee intellectual potential should be noticed and used. The subjective approach to employees is fully reflected in the empowerment process. The definition scope of the analysed notion has not been unambiguously delineated to date. In narrow terms, empowerment means delegating power in the decision-making process and is considered a management method. In broad terms, in turn, the idea is at times called even a management concept. The aim of this paper is to provide answers to the following research questions: Can empowerment be called a separate management concept? What is the awareness of the essence of empowerment among contemporary employees? What are the barriers to implementing empowerment assumptions in enterprises? The research process was based on literature studies and empirical research that was conducted in Poland under two separate research projects. One, carried out in the period 2006-2015, was oriented towards assessing the level of interest in employee participation and identifying the approach to implementing such participation in enterprises. The research covered over 300 respondents. It used structured interview complemented with free interview and analysis of the provided documents of the respondents' enterprises. The results of the research encouraged a closer look at the category of empowerment. Pilot empirical research on the category of empowerment was conducted in 2016 with questionnaire surveys. The research sample was 63 employees. It was found that empowerment should be perceived as certain expansion of employee participation rather than a separate management concept. It consisted in sharing not only information but also power with employees. The results of the empirical research permitted the ascertainment that interest in lower participation forms prevailed among the respondents. Barriers related to applying empowerment were sought in this context. The pilot research allowed a conclusion that the barriers should be sought primarily in the failure to prepare (also mentally) employees and employers for using empowerment. Although the presented results of the research are not representative, they encourage further in-depth research within the discussed area.
Keywords: M12; 330; employee empowerment; human resource management; employee participation